Understanding the concept of percent using the egg rack - E.I Pusta Siligar; Hendra Lesmana; Mewa Zabeta (Intelektual Pustaka Media Utama, 2022)
This study aimed to produce a learning path that can help students understand the concept of percent using the context of an egg rack. This study used a design research method through the Indonesian Realistic Mathematics Education approach which was carried out at Elementary School No. 2 Gumawang, Indonesia. Data were obtained through observation, photos, video recordings, student activity sheets, and field documentation. The result of the research was a learning trajectory consisting of three activities; first, students explore their knowledge of egg racks which are very close to students' self-life, secondly, students change the problem into a bar form based on students' knowledge of egg racks, then students change the problem into fractions and students change the fraction with the denominator one hundred, third, students solve the percent problem in a more complicated form. The activities that have been produced and tested on percent learning using the context of an egg rack, can help students to better understand the concept of percent.